(3Yde GdEgJOGA aj eYQaI Gdhba hGdEHJOGAs - (3eMeO Hf eMeO Hf Ydj Hf geGe Hf GdGeGe, CHh YHO Gddg,J (B745 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje, MOKfj GdEeGe CHhGdaVd eMeO Hf jhSa Yf Ce SdeI bGdJ Cf QShd Gddg Udi Gddg Ydjg hSde jbWY bQGAJg Hbhd GdMeO ddg QH GdYGdejf Ke jba s
(3BNQgG (B:s
(3Gddge dG JNdfG ef EMSGfc hhaQ fUjHfG ef aVdc Je GdcJGH s
(3GdfSNI HgG MhGTs
(3Ydjg bQGAI SfI (B734 (3g`s
(3hbO ofSH gPG GdeNWhW CjVkG aj cTa GdXfhf ddSNGhjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1160s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs